Conceptualizing care partners' burden, stress, and support for reintegrating Veterans: a mixed methods study - Rattray, Nicholas A.; Flanagan, Mindy; Mann, Allison; Danson, Leah; Do, Ai-Nghia; Natividad, Diana; Spontak, Katrina; True, Gala (Frontiers in Public Health, 2024)
Background People who support Veterans as they transition from their military service into civilian life may be at an increased risk of psychological distress. Existing studies focus primarily on paid family caregivers, but few studies include spouses and informal non-family “care partners.” We sought to identify key challenges faced by care partners of Veterans with invisible injuries. Methods Semi-structured interviews were conducted with 36 individuals involved in supporting a recently separated US military Veteran enrolled in a 2-year longitudinal study. CPs completed validated measures on perceived stress, caregiving burden, quality of their relationship, life satisfaction, and flourishing. Independent t-tests were used to compare cases in these groups on caregiving burden, quality of their relationship, life satisfaction, and flourishing. Care partners were categorized as reporting high and low levels of stress. Exemplar cases were used to demonstrate divergences in the experiences of CPs with different levels of stress over time. Results Care partners reported shifts in self-perception that occurred from supporting a Veteran, emphasizing how they helped Veterans navigate health systems and the processes of disclosing health and personal information in civilian contexts. Exemplar cases with high and low burdens demonstrated divergent experiences in self-perception, managing multi-faceted strain, and coping with stress over time. Case studies of specific care partners illustrate how multi-faceted strain shifted over time and is affected by additional burdens from childcare, financial responsibilities, or lack of education on mental health issues. Conclusions Findings suggest the unique needs of individuals who support military Veterans with invisible injuries, highlighting variations and diachronic elements of caregiving. This sample is younger than the typical caregiver sample with implications for how best to support unpaid care partners caring for Veterans in the early to mid-period of their use of VA and civilian health services.